2007
DOI: 10.1080/07420520701535787
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and Coronary Heart Disease Deaths in United States Firefighters

Abstract: United States firefighters have a high on-duty fatality rate and coronary heart disease is the leading cause. Seasonality affects the incidence of cardiovascular events in the general population, but its effects on firefighters are unknown. We statistically examined the seasonal and annual variation of all on-duty coronary heart disease deaths among US firefighters between 1994 and 2004 using the chi-square distribution and Poisson regression model of the monthly fatality counts. We also examined the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
(33 reference statements)
1
15
0
1
Order By: Relevance
“…These results cannot be directly compared to the risk functions developed to quantify the association between outdoor heat and mortality (Mbanu et al, 2007;Mirabelli and Richardson, 2005), because our model was developed essentially on non-fatal heat illnesses (6 fatalities for 259 heat illnesses). Comparison of our results with those of studies on morbidity performed in other latitudes may also be difficult, as hot temperature thresholds for morbidity appear to vary by location (Ye et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results cannot be directly compared to the risk functions developed to quantify the association between outdoor heat and mortality (Mbanu et al, 2007;Mirabelli and Richardson, 2005), because our model was developed essentially on non-fatal heat illnesses (6 fatalities for 259 heat illnesses). Comparison of our results with those of studies on morbidity performed in other latitudes may also be difficult, as hot temperature thresholds for morbidity appear to vary by location (Ye et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The risk function for the association between average summer temperatures and the number of occupational heat-related deaths was estimated in two studies; in the United States, the risk of on-duty coronary heart disease mortality among firefighters was not associated with increasing temperatures during months with average temperatures above 5 1C, between 1994 and 2004 (Mbanu et al, 2007), while in the whole working population of North Carolina between 1977 and 2001, the rate of heat-related death increased by 37% for each 1 1F increase (corresponding to approximately 77% per 1 1C increase) in average summer temperatures (Mirabelli and Richardson, 2005). In addition, only one pilot study, carried out by the Florida Department of Health (2012) between 2005 and 2009, reported a quantitative relationship between average summer temperatures and heat-related hospitalizations and emergency department visits, where cases were stratified in occupational and non-occupational groups.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of an association between firefighting and death from cardiovascular disease,15 16 and evidence of an increase in cardiac mortality particularly close to an alarm or turn-out 9 16 17…”
Section: Introductionmentioning
confidence: 99%
“…Attention should be paid also to the potential role of climate and latitude as possible synchronizers or sources of masking effects, especially in the conduct of chronoepidemiological and seasonality studies (Arendt, 2006;Higuchi et al, 2007;Mbanu et al, 2007;Radun & Radun, 2006;Shah et al, 2006). Papers entailing shift-work research must also clearly define the work schedule and duties of the workers (e.g., Camerino et al, 2008;Eriksen et al, 2006;Jay et al, 2006;Lammers-van der Holst et al, 2006;Persson et al, 2006;Thorne et al, 2008).…”
Section: Chronobiological Criteriamentioning
confidence: 98%